Leadership strategy and its impact on the development of distinguished performance among the heads of departments of the faculties of physical education and sports sciences (Journal of the College of Basic Education, 2022)
The research included the definition of the research, the introduction, and the importance of the research. The problem of the study was represented in the following question (leadership strategy and its impact on the development of administrative excellence among the heads of departments of the faculties of physical education and sports sciences).